Cigarette smoking and mammographic breast density in post-menopausal women from the EPIC Florence cohort - Bendinelli, Benedetta; Caini, Saverio; Assedi, Melania; Ermini, Ilaria; Pastore, Elisa; Facchini, Luigi; Gilio, Maria Antonietta; Duroni, Giacomo; Fontana, Miriam; Querci, Andrea; Ambrogetti, Daniela; Saieva, Calogero; et al. (Frontiers in Oncology, 2024)
Cigarette smoking has been recognized as a risk factor for breast cancer (BC) also if the biological mechanism remains poorly understood. High mammographic breast density (MBD) is associated with BC risk and many BC risk factors, such as genetic, anthropometric, reproductive and lifestyle factors and age, are also able to modulate MBD.The aim of the present study was to prospectively explore, in post-menopausal women, the association between smoking habits and MBD, assessed using an automated software, considering duration and intensity of smoking.The analysis was carried out in 3,774 women enrolled in the European Prospective Investigation into Cancer and Nutrition (EPIC) Florence cohort in 1993-98, participating in the 2004-06 follow up (FU) and with at least one full-field digital mammography (FFDM) performed after FU. For each woman, detailed information on smoking habits, anthropometry, lifestyle and reproductive history was collected at enrollment and at FU. Smoking information at baseline and at FU was integrated. The fully automated Volpara TM software was used to obtain total breast volume (cm 3 ), absolute breast dense volume (DV, cm 3 ) and volumetric percent density (VPD, %) from the first available FFDM (average 5.3 years from FU). Multivariable linear regression models were applied to evaluate the associations between smoking habits and VPD or DV.An inverse association between smoking exposure and VPD emerged (Diff% -7.96%, p <0.0001 for current smokers and -3.92%, p 0.01 for former smokers, compared with non smokers). An inverse dose-response relationship with number of cigarettes/day, years of smoking duration and lifetime smoking exposure (pack-years) and a direct association with time since smoking cessation among former smokers emerged. Similar associations, with an attenuated effect, emerged when DV was considerd as the outcome variable. This longitudinal study confirms the inverse association between active smoking, a known risk factor for BC, and MBD among post menopausal women. The inclusion of smoking habits in the existing BC risk prediction models could be evaluated in future studies.